Formulation of peel-off mask loaded with blue emissive carbon dots from Hylocereus polyrhizus peels as a UV-blocking active agent - Muhammad Nazar; Muhammad Hasan; Maulida Maghfira; Sefirra Mustiqillah; Cut Elvira Nada; Syahrial Syahrial; Kana Puspita; Rusman Rusman; Noor Hana Hanif Abu Bakar; Wael Saud Althubaiti (Results in Engineering)
This study explores the formulation, characterization, and subjective evaluation of peel-off masks enriched with Carbon Dots (CDs) derived from Hylocereus polyrhizus peels via a hydrothermal synthesis method. Photoluminescent properties of both the CDs and the formulated masks were confirmed through photo analysis. The masks demonstrated sun protection factors (SPF) ranging from 8.104 to 9.090. All formulations exhibited favorable pH levels between 4.6 and 5.6, excellent homogeneity, viscosities between 14,300 and 22,500 cPs, drying times of 25.05 to 30.01 minutes, and spreadability values of 5.4 to 6.3 cm. Subjective evaluations identified the F3 formulation as the most preferred. The successful incorporation of CDs from red dragon fruit peel into peel-off masks highlights their potential for UV protection and user satisfaction.